2008
DOI: 10.1007/s11357-008-9046-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of hyl-1, the C. elegans homolog of LAG1/LASS1

Abstract: Yeast LAG1 was one of the first longevity genes found. Subsequent analysis showed that it encodes a component of ceramide synthase. Homologs of LAG1 have been identified in all eukaryotes examined for their presence, and multiple homologs are the norm. In human and mouse, the LAG1 counterpart is called LASS1. The involvement of this gene in determining yeast replicative life span led us to ask whether longevity effects could be found in C. elegans. Extended longevity was seen when we used RNAi to decrease expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…HYL-2 synthesizes a ceramide homolog that has a pro-survival effect, while the ceramide generated by Lag1 homolog HYL-1 has an apoptotic effect 103 . This is consistent with the lifespan extension seen in the roundworm on knockdown of hyl-1 105 .…”
Section: Retrograde Response In Other Organismssupporting
confidence: 88%
“…HYL-2 synthesizes a ceramide homolog that has a pro-survival effect, while the ceramide generated by Lag1 homolog HYL-1 has an apoptotic effect 103 . This is consistent with the lifespan extension seen in the roundworm on knockdown of hyl-1 105 .…”
Section: Retrograde Response In Other Organismssupporting
confidence: 88%
“…Several studies reported that no single deletion of any of the three C. elegans CerS genes resulted in life span extension (Deng et al, 2008, Tedesco et al, 2008, Menuz et al, 2009), but rather deletion of hyl-2 reduced life span slightly (Mosbech et al, 2013). By switching to an RNAi feeding approach, however, to target the Lag1p motif in hyl-1, Tedesco and coworkers observed a small (about 15%) but reproducible increase in longevity (Tedesco et al, 2008). It is notable that the longevity effect of hyl-1 RNAi is accompanied by significant reduction of mRNA levels of both hyl-1 and hyl-2, so it was possible that both hyl-1 and hyl-2 functions were reduced by targeting the shared Lag1p motif after RNAi.…”
Section: Elegans Serine Palmitoyltransferase (Spt)mentioning
confidence: 99%
“…In C. elegans the sphingolipids are of less structural complexity as the sphingoid long chain base exclusively constitutes a C17 iso - or anteiso -branched chain as illustrated in Figure S1. C. elegans comprises three ceramide synthases HYL-1, HYL-2, and LAGR-1, each containing a Lag1p motif required for ceramide synthase activity [6], [7]. It has been shown that radiation-induced apoptosis in the germ line is inhibited in hyl-1(ok976) , lagr-1(gk327/gk331) , and hyl-1(ok976);lagr-1(gk327) animals, which can be relieved by injection of C16 ceramide [8].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hyl-2(gnv1) animals contain less C20-22 ceramides and sphingomyelins but more with C24-26. Tedesco et al [7] recently showed that RNAi targeted against the Lag1p motif in hyl-1 extended lifespan and reduced mRNA levels of both hyl-1 and hyl-2 , while hyl-1 deletion mutants ( hyl-1(ok976/gk203)) showed no alterations in lifespan and an increased level of hyl-2 mRNA.…”
Section: Introductionmentioning
confidence: 99%